2009
DOI: 10.2116/analsci.25.993
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Circular Double-Stranded DNA Having Single-Stranded Recognition Sequence as molecular-Physical Probe for Nucleic Acid Hybridization Detection Based on Atomic Force microscopy Imaging

Abstract: A new class of DNA probes having a mechanically detectable tag is reported. The DNA probe, which consists of a single-stranded recognition sequence and a double-stranded circular DNA entity, was prepared by polymerase reaction. M13mp18 single strand and a 32mer oligodeoxynucleotide whose 5′-end is decorated with the recognition sequence were used in combination as template and primer, respectively. We have successfully demonstrated that the DNA probe is useful for bioanalytical purposes: by deliberately attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We found that, using this particular feature, simple histogram analysis could allow convenient quantification. 21,22 Figure 4 explains each frequency distribution fundamentally traces a specific curve typical of a normal distribution. Nonlinear curve fitting assuming a set of multiple Gaussian function peaks was also performed; the results are summarized in Table 2.…”
Section: Surface Roughness Analysis and Sensitivity Of Detectionmentioning
confidence: 99%
“…We found that, using this particular feature, simple histogram analysis could allow convenient quantification. 21,22 Figure 4 explains each frequency distribution fundamentally traces a specific curve typical of a normal distribution. Nonlinear curve fitting assuming a set of multiple Gaussian function peaks was also performed; the results are summarized in Table 2.…”
Section: Surface Roughness Analysis and Sensitivity Of Detectionmentioning
confidence: 99%